Male friendship, homosociality, and women in the Hebrew Bible: malignant fraternities - Thiede, Barbara (Routledge studies in the biblical world, 2022)
Introduction. Honesty, transparency, and sight: some introduction -- Chapter 1. Genesis 38: "Lest we become a laughingstock" -- Chapter 2. David, Jonathan, and Saul: being good at being a man -- Chapter 3. 2 Samuel 13: rape in the royal house -- Chapter 4. Genesis 12, 20, and 26: Bromance in the Bible -- Chapter 5. Judges 19-21: The warrior God and his Levite soldier -- Chapter 6. Judges 4 & 5: Always mothers, never friends -- Conclusion. Toxic for women: conclusions on biblical hegemonic masculinity.